The Value of Quantitative Musculoskeletal Imaging - Visser, Jacob J.; Goergen, Stacy K.; Klein, Stefan; Noguerol, Teodoro Martín; Pickhardt, Perry J.; Fayad, Laura M.; Omoumi, Patrick (Seminars in Musculoskeletal Radiology, 2020)
Musculoskeletal imaging is mainly based on the subjective and qualitative analysis of imaging examinations. However, integration of quantitative assessment of imaging data could increase the value of imaging in both research and clinical practice. Some imaging modalities, such as perfusion magnetic resonance imaging (MRI), diffusion MRI, or T2 mapping, are intrinsically quantitative. But conventional morphological imaging can also be analyzed through the quantification of various parameters. The quantitative data retrieved from imaging examinations can serve as biomarkers and be used to support diagnosis, determine patient prognosis, or monitor therapy.We focus on the value, or clinical utility, of quantitative imaging in the musculoskeletal field. There is currently a trend to move from volume- to value-based payments. This review contains definitions and examines the role that quantitative imaging may play in the implementation of value-based health care. The influence of artificial intelligence on the value of quantitative musculoskeletal imaging is also discussed.
Keywords: quantitative imaging; musculoskeletal imaging; imaging biomarkers; clinical utility; value-based health care